Assessment of Heavy Metal Contamination in Water and Sediment to Support Environmental Monitoring of a Mining-Affected River in Buper Waena, Papua, Indonesia - Vyona Mantayborbir; Lalu Panji Imam Agamawan; Ervina Indrayani; Dirk Y. P. Runtuboi; Yulindra Margaretha Numberi; Fawuni G. A. G. Rumbrawer (Ali Institute of Research and Publication, 2026)
Artisanal mining activities are recognized as important sources of heavy metal contamination in river ecosystems. This study evaluated cadmium (Cd), lead (Pb), and mercury (Hg) concentrations in water and sediments of Kali Jembatan Dua, Jayapura, Papua, Indonesia, as baseline information for environmental monitoring. Water and sediment samples were collected from three stations representing upstream mining areas and downstream river sections in June 2025. Heavy metal concentrations were analyzed using Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). Concentrations in water ranged from 0.076-0.313 mg/L for Cd, 0.0032-0.0076 mg/L for Pb, and 0.0014-0.0039 mg/L for Hg. Cadmium exceeded the applicable Indonesian water quality standard, whereas Pb and Hg concentrations varied according to the designated water-use classification. Sediment concentrations ranged from 0.347-0.894 mg/kg (Cd), 0.721-2.234 mg/kg (Pb), and 0.0165-0.0277 mg/kg (Hg). Metal concentrations were generally higher at stations near mining activities and lower downstream. Sediments contained higher metal concentrations than the water column, indicating their role as sinks and potential secondary sources of contamination. These findings highlight the need for continuous monitoring and management of mining-affected river systems in Papua.